Experimental and Finite Element Analysis of the Pressure Carrying Capacity of Reinforced Composite Thick-Walled Material Tubes - Hamed, Abdalla F. (2009)
Presently modern composites using continuous fibers in a resin matrix are important candidate materials for cylindrical structures like pipes and pressure vessels. These materials are lighter, stronger, corrosion resistance and more cost effective when compared with the traditional materials like metals. These structures are commonly subjected to internal pressure and there are some applications where structures subjected to complex loading conditions which are resulted from internal pressurization and superimposed axial loads during installation and/or operation. Most of the previous works were concentrated on the thin shell structures while less work was carried out on thick shell structures under internal pressure loading. The use of hybrid structures in this application is limited and also a limited research work is available for multi-directional tubular composite structures compared with single lay-up configuration. The effects of the different winding angle, different materials and hybridization, different number of layers and different stacking sequence of multi-layered angles on the carrying capacity of thick shell composite tube under internal pressure loading have been studied. The composite materials used were glass/epoxy and carbon/epoxy. In this study it was found that the optimum winding angle for filament wound pipes depends primarily on the loading modes applied. The experimental results showed that the optimum winding angle is 550 for biaxial pressure loading (mode II), 750 for hoop pressure loading (mode I) while 850 is suitable for biaxial pressure with axial compressive loading (mode III). The test results also show that the carrying capacity of the composite tube increases as the number of the number of layers increase and the percentage difference for all loading modes is about 46% and 63% for four layers and six layers compared by two layers of glass/epoxy respectively. Changing the stacking sequence of multi-layered composite tube enhance the internal pressure carrying capacity for different loading modes and the percentage difference for all loading modes is about 5% and 13%. Using different materials for the composite tube shows that the internal pressure carrying capacity is enhanced. The carrying capacity is about 9% to 19% increased if hybrid composite tube made from two different materials; glass/epoxy and carbon/epoxy are used compared with composite tube made from glass/epoxy alone for all loading modes. On the other hand the carrying capacity is increased by 32% to 38% for the composite tube wound with two and four layers of carbon/epoxy compared with composite tube wound with two and four layers of glass/epoxy for all loading modes. The finite element analysis has been used to analyze the composite tube under internal pressure load for different loading modes. ANSYS finite element software was used to perform the numerical analysis for the different arrangements of composite tubes. The predicted results gave good agreement with the experimental results, the percentage differences between the experimental and the finite element analysis results are approximately 4%-25% for different loading modes.